EVALUATION OF ANTIOXIDANT AND ANTIACETYLCHOLINESTERASE ACTIVITIES OF THE EXTRACTS OF PISTACIA ATLANTICA DESF. LEAVES - Peksel, Aysegul; Arisan-Atac, Inci; Yanardag, Refiye (WILEY, 2010)
Pistacia atlantica Desf. (Anacardiaceae), a tree that is widely distributed in the Marmara, Mediterranean and Central Anatolia regions of Turkey, has been utilized traditionally for culinary and medicinal purposes. In the present study, methanolic and ethyl acetate extracts were prepared from young leaves of P. atlantica Desf., which were collected during the spring, and their antioxidant, scavenging, chelating and anti-acetylcholinesterase activities were evaluated. Both of the extracts showed strong antioxidant activity compared to synthetic antioxidants such as butylated hydroxyanisole, butylated hydroxytoluene and alpha-tocopherol whereas they exhibited relatively lower level of anti-acetylcholinesterase activity. The acetylcholinesterase inhibitory effect of the ethylacetate extract was higher than the inhibitory effect of the methanolic extract. Therefore, the extracts of the young leaves of P. atlantica Desf. might be a potential antioxidant supplement for food and pharmaceutical products. It might also be used to stabilize the foods against oxidative deterioration. PRACTICAL APPLICATIONS Pistacia atlantica Desf. (Anacardiaceae) is a tree located in the Marmara, Mediterranean and Central Anatolia regions of Turkey. The genus Pistacia includes at least 11 species. The mastic obtained from Pistacia species has been used as urinary and respiratory antiseptic in Turkish folk medicine. During the spring, the young leaves of P. atlantica Desf. are used as a vegetable and commonly consumed as cooked food in the Mediterranean and East Anatolian parts of Turkey. Pistacia species have been reported to posses anti-inflammatory, antipyretic, antifungal, antimicrobial, antiviral, anti-insect, anti-atherogenic, hypoglycemic, anticancer and hepatoprotective activities. The aerial parts and/or resin of the plant has been also used in traditional medicine for the treatment of eczema, paralysis, diarrhea, throat infections, renal stones, jaundice, asthma and stomach ache, and also as an astringent and a pectoral stimulant. According to our results, the high antioxidant properties of the leaves of P. atlantica Desf. might be beneficial to the antioxidant protection system of the human body against oxidative damage.
Keywords: IN-VITRO; L.; ACETYLCHOLINESTERASE; POLYPHENOLS; INHIBITION; PREVENTION; LENTISCUS; OXIDATION; SEEDS; Biochemistry & Molecular Biology; Food Science & Technology